2019
DOI: 10.1002/iub.2203
|View full text |Cite
|
Sign up to set email alerts
|

Albumin domain mutants with enhanced Aβ binding capacity identified by phage display analysis for application in various peripheral Aβ elimination approaches of Alzheimer's disease treatment

Abstract: Deposition of amyloid protein, particularly Aβ1‐42, is a major contributor to the onset of Alzheimer's disease (AD). However, almost no deposition of Aβ in the peripheral tissues could be found. Human serum albumin (HSA), the most abundant protein in the blood, has been reported to inhibit amyloid formation through binding Aβ, which is believed to play an important role in the peripheral clearance of Aβ. We identified the Aβ binding site on HSA and developed HSA mutants with high binding capacities for Aβ usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 53 publications
0
3
0
1
Order By: Relevance
“…Numerous studies have shown that human serum albumin targets both species [ 259 ] and inhibits amyloid-β fibrillization both in vitro [ 263 ] and in vivo [ 259 , 264 ], supporting the peripheral sink hypothesis. This strategy is based on the idea that amyloid-β in the brain and peripheral are in equilibrium and that reducing amyloid-β in the periphery can lead to a reduction of amyloid-β in the brain through passive diffusion down a concentration gradient [ 265 , 266 ].…”
Section: Amyloid-β Clearance In the Peripherymentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that human serum albumin targets both species [ 259 ] and inhibits amyloid-β fibrillization both in vitro [ 263 ] and in vivo [ 259 , 264 ], supporting the peripheral sink hypothesis. This strategy is based on the idea that amyloid-β in the brain and peripheral are in equilibrium and that reducing amyloid-β in the periphery can lead to a reduction of amyloid-β in the brain through passive diffusion down a concentration gradient [ 265 , 266 ].…”
Section: Amyloid-β Clearance In the Peripherymentioning
confidence: 99%
“…In addition to immunotherapy, non-immune approaches, such as peripheral amyloid-β-binding agents (e.g., gelsolin, GM1, sRAGE, sLRP fragments) [ 215 , 335 ], blood cells, and protein [ 248 , 265 ], have also made significant progress in disease prevention.…”
Section: Therapeutic Strategies For Clearing Amyloid-β In the Brain A...mentioning
confidence: 99%
“…Other promising direction for development of new therapeutic and preventive approaches for AD is search for HSA modifications increasing its affinity to Aβ. For example, it was shown, that the set of HSA Domain II mutants is characterized by high affinity to Aβ [27]. At the same time, mutant forms are potentially able of shifting the balance between the CNS and peripheral blood flow more efficiently than the wild type enhancing the Aβ clearance from the brain of AD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Для спорадических форм БА характерны повышение продукции и снижение скорости выведения β-амилоидного пептида (Aβ). В ряде исследований в качестве перспективной мишени для разработки новых подходов к терапии и профилактике БА рассматривается человеческий сывороточный альбумин (ЧСА), играющий роль депо Aβ в периферическом кровотоке [5,11]. Усиление взаимодействия ЧСА с Aβ должно способствовать сдвигу равновесия между периферическим кровотоком и центральной нервной системой в сторону выведения Aβ.…”
Section: Introductionunclassified